The Burden of Family Caregivers in the Care of Type 2 Diabetes Mellitus Patients: A Literature Review - Setyoadi; Meiliana, Sindy Wahyuarista; Hakim, Faradinanta Oktavia; Hayati, Yati Sri; Kristianingrum, Niko Dima; Kartika, Annisa Wuri; Sandi, Prinovi Sapta (Journal of Rural Community Nursing Practice, 2024)
Background: This literature review study is based on the increasing number of people with Type 2 Diabetes mellitus (DMT2) which has an impact on the burden of family caregivers. Chronic T2DM disease requires long-term treatment and has an impact on the physical, psychological, social, and economic family. The burden of family caregivers causes stress, burnout, helplessness, and depression. Purpose: This literature review is intended to analyze the burden of family caregivers experienced when helping to care for family members with T2DM. Methods: This study method uses a literature review design conducted on 10 articles obtained from 3 data bases, namely EBSCO, PubMed, and Science Direct. The keywords used in article searches are "family burden OR burnout" or "caregiver burden OR burnout", AND "type 2 diabetes mellitus" with "AND" and "OR" as Boolean operators. Results: The results of the literature review found that family caregivers who do not have enough knowledge and skills in caring for family members with DMT2 and get this unprecedented patient condition cause family caregivers stress and discomfort, bringing them to mental, physical, social, and economic burdens because the only thing that concerns them is how they will persist in the face of the current conditions they are experiencing as well as the future of the family. Conclusions: The importance of the role of family nurses in providing upport in unraveling the burden experienced by family caregivers.